Performance assessment of an earthquake-based optimally designed fluid viscous damper under blast loading. Issue 14 (October 2019) - Dadkhah, Hamed; Mohebbi, Mohtasham
Terrorist attacks and explosion devices are one of the growing worldwide threats which seriously threaten the safety of strategic structures. The aim of this study is assessing the performance of the linear fluid viscous damper optimally designed based on seismic loading under blast loading. To this end, the control system is first optimally designed under different earthquakes and the performance of the optimally designed fluid viscous damper is evaluated under different external blast scenarios. In order to design the optimal fluid viscous damper for seismic loading, the design problem is transformed into an optimization problem that the genetic algorithm has been used to solve the optimization problem and determine the optimal values of design variables. The fluid viscous damper configuration including size and distribution has been considered as the design variables and the design objective has been defined to keep the structure behavior in the elastic range with a minimum control cost. The optimization results show that the total added optimal damping is dependent on earthquake record, while in this case study the optimal distributions of the fluid viscous damper under earthquake records are not so different. The performance assessment of the earthquake-based optimally designed fluid viscous damper under blast loading shows its effectiveness in achieving the desired design objective. Therefore, in this case study, the fluid viscous damper designed for seismic loading can be considered as a well-designed control system under multi-hazard of blast and earthquake.